Biodegradasi Minyak Bumi oleh Mikroba pada Media Air Laut dan Air Tawar - OETOMO, DWI (Universitas Sebelas Maret, 2015)
Biodegradation of crude oil depends on the kind of microbe and capability of microbe in the process of biodegradation. Results of the microbe isolate from the aquatic environment polluted by crode oil have varying capabilities. Some of the microbe isolates, such as Pseudomonas sp., Staphylococcus sp., Bacillus sp., Nocardia sp., Vibrio sp. and Mycobacterium sp. could live and use erode oil as source.of carbon and energy. Hydrocarbon in crude oil was used as source of carbon. Biodegradation of crude oil did not depend on sea and freshwater. Pseudomonas sp. and the mixed of all microbe isolates can degrade the crude oil more effective than the other single species of microbe. Keywords: Biodegradation, microbe isolate, crude oil, seawater, freshwater